Ocean acidification in Canada: the current state of knowledge and pathways for action - Kristina M. Barclay; Helen J. Gurney-Smith; Mohamed Ahmed; James R. Christian; Frédéric Cyr; Patrick J. Duke; Brent G. T. Else; Iria Gimenez; Martine Lizotte; M. Catherine Reader; Myron Roth; Krysten Rutherford; et al. (Frontiers in Marine Science, 2026)
Ocean acidification (OA) generally receives far less consideration than other climate stressors and related hazards, such as global warming and extreme weather events. Canada is uniquely vulnerable to OA given its extensive coastal oceans, the oceanographic processes in its three basins, accelerated warming and sea-ice melt, and extensive coastal communities and maritime economic sectors. Canada’s coastline is also home to extensive and diverse First Nations peoples with distinct histories, rights, title, laws, governance and whose traditions and cultures are extrinsically linked to the sea. However, there are currently very limited pathways to support OA action, mitigation, and/or adaptation in Canada, particularly at the policy level. Here, we present a first synthesis of the current state of OA knowledge across Canada's Pacific, Arctic, and Atlantic regions, including monitoring, modelling, biological responses, socioeconomic and policy perspectives, and examples of existing OA actions and efforts at local and provincial levels. We also suggest a step-wise pathway for actions to enhance the coordinated filling of OA knowledge gaps and integration of OA knowledge into decision-making frameworks. The goals of these recommendations are to improve our ability to respond to OA in Canada, and minimize risks to coastal marine environments and ecosystems, vulnerable sectors, and communities.

Growth impacts in a changing ocean: insights from two coral reef fishes in an extreme environment - Daniele D’Agostino; John A. Burt; Veronica Santinelli; Grace O. Vaughan; Ashley M. Fowler; Tom Reader; Brett M. Taylor; Andrew S. Hoey; Geórgenes H. Cavalcante; Andrew G. Bauman; David A. Feary (Coral Reefs, 2021)
Determining the life-history consequences for fishes living in extreme and variable environments will be vital in predicting the likely impacts of ongoing climate change on reef fish demography. Here, we compare size-at-age and maximum body size of two common reef fish species ( Lutjanus ehrenbergii and Pomacanthus maculosus ) between the environmentally extreme Arabian/Persian Gulf (‘Arabian Gulf’) and adjacent comparably benign Oman Sea. Additionally, we use otolith increment width profiles to investigate the influence of temperature, salinity and productivity on the individual growth rates. Individuals of both species showed smaller size-at-age and lower maximum size in the Arabian Gulf compared to conspecifics in the less extreme and less variable environment of the Oman Sea, suggesting a life-history trade-off between size and metabolic demands. Salinity was the best environmental predictor of interannual growth across species and regions, with low growth corresponding to more saline conditions. However, salinity had a weaker negative effect on interannual growth of fishes in the Arabian Gulf than in the Oman Sea, indicating Arabian Gulf populations may be better able to acclimate to changing environmental conditions. Temperature had a weak positive effect on the interannual growth of fishes in the Arabian Gulf, suggesting that these populations may still be living within their thermal windows. Our results highlight the potential importance of osmoregulatory cost in impacting growth, and the need to consider the effect of multiple stressors when investigating the consequences of future climate change on fish demography.

Comparative analysis of the N-genome in diploid and polyploid Aegilops species - Ekaterina D. Badaeva; Olga S. Dedkova; Svyatoslav A. Zoshchuk; Alexandra V. Amosova; Stephen M. Reader; Michel Bernard; Alexander V. Zelenin (Chromosome Research, 2011)

Comparative genetic analysis of the Aegilops longissima and Ae. sharonensis genomes with common wheat - H. Zhang; S. M. Reader; X. Liu; J. Z. Jia; M. D. Gale; K. M. Devos (Theoretical and Applied Genetics, 2001)

Characterization of Aegilops uniaristata chromosomes by comparative DNA marker analysis and repetitive DNA sequence in situ hybridization - N. Iqbal; S. M. Reader; P. D. S. Caligari; T. E. Miller (Theoretical and Applied Genetics, 2000)

Present-day hulled wheats from Spain - T. E. Miller; E. J. Lamont; L. Peña-Chocarro; S. M. Reader; M. J. Ambrose (Cereal Research Communications, 1999)

Chromosome aberrations in wheat nullisomic-tetrasomic and ditelosomic lines - K. M. Devos; M. E. Sorrells; J. A. Anderson; T. E. Miller; S. M. Reader; A. J. Lukaszewski; J. Dubcovsky; P. J. Sharp; J. Faris; M. D. Gale (Cereal Research Communications, 1999)

Chromosomal location of genes coding for endosperm proteins of Hordeum chilense, determined by two-dimensional electrophoresis of wheat-H. chilense chromosome addition lines - P. I. Payne; L. M. Holt; S. M. Reader; T. E. Miller (Biochemical Genetics, 1987)